An In-depth Study of How Rahim Shah Learned to Speak English and Persian Better Than His Native Language: An Explanatory Case Study - Asghari, Ghulam Yahya; Ramish, Rahimullah; Zawuli, Ali Akbar (International Journal of Language and Literary Studies, 2022)
This mixed-methods case study explores how Rahim Shah learned to speak English and Persian much more fluently than his native language (Pashto). In this study, different aspects of the subject- including his personality, language learning style, language learning history, oral and written language skills- are analyzed to seek patterns and causes of behavior. Accordingly, attempts have been made in this paper to enlighten his exposure to three languages, Pashto (native), Persian (second) and English (foreign). The results drew that he speaks Persian much more confident than his native language mainly because his parents moved to a Persian-speaking community when he was a child of three years old. This makes it clear that non-native speakers use their knowledge of the new language through interaction with others. The results also recovered that he learned how to speak English better than his native language mainly because he was intrinsically motivated, knowing the positive consequences of learning English. In addition to his high motivation, he consistently listened to native speakers as he spent three years with Americans. Therefore, this case study embraces nearly all the aspects of how Rahim Shah managed to speak English and Persian, and how he failed to speak his native language.